2015
DOI: 10.4081/monaldi.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team in cardiac rehabilitation and secondary prevention, from the assessment to the education: an educational project

Abstract: The authors explain the training project: "Multidisciplinarity in cardiac rehabilitation and secondary prevention: from the evaluation to the therapeutic education", the rationale and purpose of a pathway for patients with ischemic heart disease treated in the acute phase with both medical and surgical means, and then placed in a rehabilitation program. The training project was transformed into a learning event for the Region of Sicily and later for the Region of Tuscany that has adopted it, encouraging the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In our study, although no significant effects on risk factors were obtained, we mention the nonnegligible decrease of LDL-cholesterol and increase of HDL-cholesterol, under the conditions of the maintenance of hypolipidemic treatment over the period between the two admissions. Data in this respect are in accordance with the literature data [15,16,17,18]. Two recent studies have demonstrated that long-term physical training has a beneficial action on cardiovascular risk factors: decrease of the body mass index by 1%, decrease of the levels of total cholesterol by 1%, triglycerides by 5%, decrease of the LDLcholesterol/HDL-cholesterol ratio by 3%, increase of HDL-cholesterol levels by 3%, improvement of psychological factors, with a reduction of the depression score by 12.6%, of the anxiety score by 4.3%, and of the hostility score by 2.3% [19,20].…”
Section: Resultssupporting
confidence: 80%
“…In our study, although no significant effects on risk factors were obtained, we mention the nonnegligible decrease of LDL-cholesterol and increase of HDL-cholesterol, under the conditions of the maintenance of hypolipidemic treatment over the period between the two admissions. Data in this respect are in accordance with the literature data [15,16,17,18]. Two recent studies have demonstrated that long-term physical training has a beneficial action on cardiovascular risk factors: decrease of the body mass index by 1%, decrease of the levels of total cholesterol by 1%, triglycerides by 5%, decrease of the LDLcholesterol/HDL-cholesterol ratio by 3%, increase of HDL-cholesterol levels by 3%, improvement of psychological factors, with a reduction of the depression score by 12.6%, of the anxiety score by 4.3%, and of the hostility score by 2.3% [19,20].…”
Section: Resultssupporting
confidence: 80%
“…The group is a specialized therapeutic group whose aim is to help patients comprehend their medical condition and discover more about its symptoms. The goal is changing patients’ perception of life and their approach to it (Da Vico et al, 2014 ; Molinari, Compare, & Parati, 2007 ). The group psychotherapist tries to support the patients and help them manage their perceived feelings and emotions, caused by their heart disease condition (Dis, 2003 ; Ghedin et al, 2017 ), through support interventions.…”
Section: Methodsmentioning
confidence: 99%